Polymer Brushes: Liquid‐Mediated Three‐Dimensional Scanning Probe Nanosculpting (Small 17/2013). Issue 17 (3rd September 2013) - Gan, Tiansheng; Zhou, Xuechang; Ma, Chunfeng; Liu, Xuqing; Xie, Zhuang; Zhang, Guangzhao; Zheng, Zijian
<x xml:space="preserve">Abstract</x> Liquid‐mediated Scanning Probe Nanosculpting (LSPN) is developed to fabricate 3D topographic structures of polymer brushes by X. C. Zhou, G. Z. Zhang, Z. J. Zheng, and co‐workers on Page 2851. LSPN makes use of a liquid solvent, to assist the AFM tip "sculpting" of polymer brushes that are fully solvated in the liquid solvent. With this method, complex structures of polymer brushes, such as 2D arrays, 3D gradients, and arbitrary 3D structures can be fabricated with sub‐10 nm resolution and 50 nm half‐pitch. This work holds great promise for the top‐down engineering of functional topographic structures on a surface towards many chemical and biological applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>